ANALISIS TINGKAT KESELAMATAN LALU LINTAS PERSIMPANGAN TAK BERSINYAL DENGAN METODE TRAFFICT CONFLICT TECHNIQUE (TCT) PADA PEREMPATAN DUREN, TANGERANG SELATAN, BANTEN - Muhammmad Daffa Naufal Labbaik (Universitas Pendidikan Indonesia (UPI), 2023)
This study was carried out at the Duren Intersection, which connects Jl. Jl. Menjangan Raya Jl. Merpati Raya Jl. Cendrawasih Raya The goal of Ki Hajar Dewantara is to examine: 1) the level of safety of unsignalized intersections by paying attention to the degree of traffic movement-related conflict; 2) the volume of vehicles at the Duren Quarter during off-peak hours; 3) the elements that contribute to accidents. The Traffic Conflict Technique (TCT) is used to analyze the data by putting oneself in a location with a high risk of accidents.The consequences of the review are as per the following: (1) There are 17 conflicts that happen with a typical chance to mishap of around 0.24 seconds. Street clients who are many times associated with clashes, to be specific motorbikes, by slowing down or dialing back the vehicle. (2) During the off top hour, the biggest number of crossing points happened on Sundays, around 5581 vehicles and loosened up on Fridays, around 4277 vehicles. (3) the variables bringing about the principal mishap, in particular the human component that didn't focus on the circumstance while going through the convergence and the second, street and natural elements, to be specific the presence of a huge contrast in street width on one arm. This causes a lopsidedness toward traffic at Duren Crossroads, bringing about a limited scale gridlock on one of the arms of the Duren crossing point.Keywords:Â Safety Level, Mishap factor, Traffic Conflict Technique (TCT), Unsignalized intersection, Vehicle Volum